Evaluation of the safety, gastroprotective activity and possible mechanisms of action of Ziziphora hispanica L. methanol extract - Amira, Hind; Mamache, Walid; Benchikh, Fatima; Benabdallah, Hassiba; Ouaret, Asma; Amira, Islam; Laouer, Hocine; Dahia, Mostefa; Amira, Aya; Demirtach, Ibrahim; Amira, Smain; Bendif, Hamdi; et al. (Elsevier, 2026)
This study aims to evaluate the gastroprotective effects of Z. hispanica methanol extract (ZME) in an ethanol-induced gastric ulcer model in rats, assess its safety profile, and investigate its chemical composition. Methods: A methanol extract was prepared by macerating 100 g of powdered aerial parts of Z. hispanica in 1000 mL of 85% methanol for 72 h. Total polyphenol content was quantified. Gastric ulcers were induced in Wistar rats using a single oral dose of 70% ethanol. Rats were pre-treated with ZME (50, 250, or 500 mg/kg) or ranitidine (50 mg/kg) as a reference control. Gastric tissues were examined for ulcerative lesions, and the percentage of protection was calculated. Gastric mucus production was also evaluated to explore the extract's mechanism of action. ZME significantly reduced ethanol-induced gastric mucosal damage in a dose-dependent manner. The highest dose (500 mg/kg) provided 97.18% protection. Additionally, ZME significantly enhanced gastric mucus secretion, exceeding that of the positive control. The extract's bioactivity is attributed to its phenol and flavonoid constituents. ZME exhibits strong gastroprotective properties by reinforcing the gastric mucus barrier. These findings validate the traditional use of Z. hispanica for gastrointestinal relief and suggest its potential as a natural therapeutic agent for the management of gastric ulcers.